Endomarketing: a key piece in the design and management of a liquid experience - Torres Pérez, Miguel E. (2022)
The customer experience has become the core of the marketing strategies of companies and brands in the current context. Today we live in a liquid society where everything changes rapidly. Competitive advantages have been displaced towards totally intangible aspects, and if the experience is considered as a totally personal phenomenon anchored in people's memory, it becomes essential to reflect on how to design and manage these experiences. A key piece in this process is endomarketing; a phenomenon relatively little studied and affected by the polysemy that marketing suffers as a discipline. With antecedents focused on the importance of internal customer service, the systemic conception of marketing from internal, external and interactive perspectives, the need to incorporate new paradigms into business practice, such as Laloux's Teal Model and the "Funky" perspective. of economies of the soul, this article attempts to provide a vision of endomarketing that serves as a reference for brands and organizations to understand that without a memorable experience inside, it is impossible to generate memorable experiences outside. The topic can be controversial and have different interpretations, however we are convinced that an effective marketing strategy cannot be developed if we do not start from here, especially in times where the human must be at the center of any proposal.